PENGARUH PENYULUHAN KESIAPSIAGAAN BENCANA BANJIR TERHADAP PENGETAHUAN KELUARGA DI KELURAHAN TUMINTING KOTA MANADO - Walanda, Irwan Eembang; Bangkut, Margareta; Hilipito, Riskawati (NHM PRESS, 2024)
Abstract - preparedness is largely determined by the influence of flood disaster counseling on family knowledge in dealing with flood disasters. This study aims to determine the preparedness and knowledge of families in the Tuminting Subdistrict, Manado City which will be conducted in April 2023. The research method is Pre-Experimental with the One-group pre-post technique as many as 64 respondents from the community affected and at high risk of flooding in the Tuminting sub-district. Manado City. The instrument used is a questionnaire. The dependent variable is flood disaster preparedness and the independent variable is family knowledge. The results of the study showed that there was a significant relationship between preparedness and knowledge of community families with the Wilcoxon test, the results were p = 0. <0.05, the conclusion that Ha was accepted, H0 was rejected. Preparedness is very important because preparedness is an action taken to prepare oneself to reduce or avoid the impact of a disaster. The more health education counseling about disasters, especially flood disasters, will make the community understand moe about preparedness for flood disasters.